HSP 60 expression in mucocutaneous lesions of Behcet's disease - DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (MOSBY, INC, 2001)
Background: Heat shock protein (60 kd HSP) has been implicated in the etiology of Behcet's disease, but its expression at sites of inflammation is unknown. Objective: Our aim was to investigate local HSP 60 expression and to quantify T-cell receptor (TCR) gamma delta -positive cells, which are known to respond to HSP peptides. Methods: Patients with active Behcet's disease (n = 21) and controls (n = 18) were included. Flow cytometric analysis was performed on peripheral blood to investigate TCR gamma delta -positive cell counts. Biopsies were performed on active skin lesions, and immunohistochemical analysis was performed by a streptavidin-biotin method using the monoclonal ML-30 antibody; HSP staining intensity and distribution were evaluated in a blinded fashion. immunhistochemical studies were performed to quantify TCR y5-positive cells at lesional sites. Results: Mucocutaneous lesions of patients with Behcet's disease had statistically significantly increased expression of HSP 60/65. Peripheral blood TCR gamma delta -positive cell counts were similar in both groups. However, lesional skin of patients with Behcet's disease had significantly increased gamma delta -positive T-cell counts. Conclusion: Up-regulation of HSP expression was found at lesional skin sites in Behcet's disease. The increased number of TCR gamma delta -positive cells, which are known to respond to HSP peptides, may support the function of HSPs in the etiology of Behcet's disease. However, these findings may also be an epiphenomenon that needs to be further investigated.
Keywords: HEAT-SHOCK-PROTEIN; T-CELL EXPANSIONS; GAMMA-DELTA; AUTOIMMUNITY; LYMPHOCYTES; RESPONSES; RECEPTOR